Exploring neonicotinoid effects on Drosophila: insights into olfactory memory, neurotransmission, and synaptic connectivity - Schulz, Julia; Franz, Hanna R.; Deimel, Stephan H.; Widmann, Annekathrin (Frontiers in Physiology, 2024)
Neonicotinoid insecticides, the fastest-growing class in recent decades, interfere with cholinergic neurotransmission by binding to the nicotinic acetylcholine receptor. This disruption affects both targeted and non-targeted insects, impairing cognitive functions such as olfaction and related behaviors, with a particular emphasis on olfactory memory due to its ecological impact. Despite the persistent presence of these chemicals in the environment, significant research gaps remain in understanding the intricate interplay between cognitive function, development, neuronal activity, and neonicotinoid-induced toxicity. This study focuses on the fruit fly Drosophila melanogaster, chosen for its genetic tractability, well-characterized neural circuitry, and remarkable parallels with bees in neurotransmitter systems and brain structures. Our aim is to establish the fruit fly as a valuable model organism for studying the effects of neonicotinoids on behavior and neuronal circuitry, with particular attention to olfactory memory and associated brain circuitries. To achieve this aim, we conducted experiments to investigate the effects of short-term exposure to sublethal doses of the neonicotinoid imidacloprid, mimicking realistic environmental insecticide exposure, on the formation of odor memories. Additionally, we evaluated synaptic contacts and cholinergic neurotransmission within the mushroom body, the primary memory network of insects. Our results showed significant impairments in odor memory formation in flies exposed to imidacloprid, with exposure during the adult stage showing more pronounced effects than exposure during the larval stage. Additionally, functional studies revealed a decrease in synaptic contacts within the intrinsic olfactory projection neurons and the mushroom body. Furthermore, another experiment showed an odor-dependent reduction in cholinergic neurotransmission within this network. In summary, employing Drosophila as a model organism provides a robust framework for investigating neonicotinoid effects and understanding their diverse impacts on insect physiology and behavior. Our study initiates the establishment of the fruit fly as a pivotal model for exploring neonicotinoid influences, shedding light on their effects on olfactory memory, neuronal integrity, and synaptic transmission.